Opportunities and challenges in sustainability of vertical farming: a review - Kalantari, Fatemeh; Mohd Tahir, Osman; Joni, Raheleh Akbari; Fatemi, Ezaz (Czech Society for Landscape Ecology, 2018)
As the world population continues to grow at a rapid rate, accompanied by a substantial growth in food demand which is expected to transpire in the next 50 years, 80 % of the population will be living in urban areas. In order to feed this growing population, there is a need for sustainable urban food. Producing sustainable urban food requires considering all factors of sustainability collectively including, environmental, social and economic advancement. A new method that has been proposed to address the issue of sustainability and to meet the growing food demand is, designing and implementing vertical farms. Vertical farming is a concept that involves cultivating plants with livestock on vertically inclined surfaces such as in skyscrapers in urban areas, where there is a lack of available land and space. However, there is a paucity of information and a limited number of published critical reviews on Vertical farming in urban areas. This study, in an attempt to review the major opportunities and challenges of Vertical Farming, uses the framework of sustainability to examine the role of it in prospective food provision in cities. This study is a critical review of 60 documents from related published papers from relevant journals and scientific online databases. Vertical Farming can be potentially beneficial in increasing food production, maintaining high quality and safety and contributing to sustainable urban farming. Well-known advantages of growing food within the urban territory can be beneficial environmentally, socially and economically. Vertical farms can also provide solutions for increasing food security worldwide.